Entrepreneurship and Innovation Events during the COVID-19 Pandemic: The User Preferences of VirBELA Virtual 3D Platform at the SHIFT Event Organized in Finland - Jauhiainen Jussi S (MDPI, 2022)
The COVID-19 pandemic brought abrupt changes for international events that promote entrepreneurship and innovation. Usually, such events bring together thousands of participants to provide them with information about ongoing and emerging trends in their fields, to network with old and new colleagues and get ideas that can develop into innovations. In 2020, most such events were cancelled. Few events were organized virtually, that is without participants physically coming together. Compared with physical face-to-face events, virtual events reduce the travel-related emissions and consumption, thereby supporting sustainability. This article studies the SHIFT entrepreneurship and innovation event held virtually in October 2020 and organized in Finland. For this article, the author gathered data about user preferences from surveying participants, speakers, presenters and organizers, almost all of whom were first-time users of VirBELA's 3D virtual platform. Furthermore, participant observation and interviews via avatars were conducted during the event. At the virtual event, 68% of respondents talked with former acquaintances, and 68% also talked with new acquaintances, and 53% opinioned that using the virtual platform can support the emergence of innovations. Virtual entrepreneurship and innovation events have potential to support networking, novel ideas and thus innovations, but issues of trust and confidentiality arose concerns among some participants.